Preimplantation Genetic Testing: Its Evolution, Where Are We Today? - Parikh, Firuza Rajesh (J Hum Reprod Sci, 2018)
Preimplantation genetic testing (PGT) is an early form of prenatal genetic diagnosis where abnormal embryos are identified, thereby allowing transfer of genetically normal embryos. This technology has become an integral part of Assisted Reproductive Technology (ART) procedures. Initial experiments with animals as early as 1890 and those in the mid and later part of the last century paved the forward path of ART and PGT. This review article covers the evolution of PGT and is a pointer toward current and fast-evolving technology, allowing scientists and doctors to better comprehend human reproduction, and ensure healthy pregnancy outcomes.